A study on liquid sourdough fermentation as affected by strain and mill fraction composition - Dorsch, Andrew Corbin (Kansas State University, 2024)
In the past few years, sourdough has seen a surge in popularity in the United States baking culture. Sourdough utilizes lactic acid producing bacteria, acetic acid producing bacteria, and yeasts to provide pH change, flavor development, and CO₂ production. The objective of this study was to determine the impact different LAB strains have on the fermentation characteristics of experimental milled wheat fractions. Hard red winter wheat was milled to create nine fractions with differing composition. To assess the compositional characteristics of the various fractions, testing was done on moisture, ash, mineral content, starch content, and damaged starch for each fraction. The fractions were then fermented using three purified strains of lactic acid producing bacteria, or LAB. The strains, distinguished as La1, La2, and La3, utilize different metabolic pathways during fermentation, which is hypothesized to result in unique fermentation characteristics. V[subscript max], T[subscript max], time to pH 4.0, minimum pH, and maximum TTA were collected by monitoring the pH and total titratable acidity during the 48-hour fermentation. The metabolites accumulated in the fermented sourdough were also quantified. The data was analyzed to determine how the various strain and fraction combinations performed, as well as how the fermentation characteristics are correlated to the fraction composition. It was determined that each of the nine fractions had unique compositions, morphology, and functional characterizations. In general, the La2 strain, which is homofermentative, was able to achieve a pH of 4.0 earlier than the other strains. La2 also had the lowest minimum pH and the highest maximum TTA. Specifically, La2 performed best when fermenting those fractions with higher amounts of endosperm. La1 and La3 are both heterofermentative bacteria and performed best when fermenting fractions with higher mineral content. Overall, the shorts fraction resulted in faster acidification and higher final acid production for all strains. It was found that the selection of both substrate and strain has a clear impact on the fermentation characteristics and sourdough characteristics when the process is held constant. These differences can help industry determine what strain or wheat fraction can be utilized to achieve a desired fermentation and sourdough characteristics outcome.
Keywords: Sourdough; Acidification; Lactic acid producing bacteria; Mill streams; Liquid fermentation